2008
DOI: 10.1139/w08-093
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of enzymatic antioxidant defence systems in different metabolic types of yeasts

Abstract: The enzymatic defence system in the 2 yeasts Kluyveromyces marxianus and Rhodotorula glutinis, differing in their mode of oxygen uptake and energy generation, was characterized and compared with the well-studied facultatively fermentative Crabtree-positive Saccharomyces cerevisiae strain. Twofold higher superoxide dismutase (SOD) and catalase activities were detected in K. marxianus and R. glutinis when cells were cultured on glucose. Further increases of 10%-15% in SOD activity and 30%-50% in catalase were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In terms of SOD activities, 90 U/mg protein was reported with Aspergillus niger (Tsekova and Todorova 2002), while 44.3 U/mg with Cordyceps militaris (Wang et al 2005) and 150 U/mg with Stenotrophomonas maltophilia (Tsekova and Todorova 2002), most of which were exposed to an oxidative stress inducer. Using R. glutinis Koleva et al (2008) reported 28 U/mg protein of SOD activity also in ethanol-containing medium, whereas we achieved 125 U/mg protein SOD activity with glycerol-containing medium. Th ese comparative results seem to be striking, since they were obtained without additional oxidative stress.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In terms of SOD activities, 90 U/mg protein was reported with Aspergillus niger (Tsekova and Todorova 2002), while 44.3 U/mg with Cordyceps militaris (Wang et al 2005) and 150 U/mg with Stenotrophomonas maltophilia (Tsekova and Todorova 2002), most of which were exposed to an oxidative stress inducer. Using R. glutinis Koleva et al (2008) reported 28 U/mg protein of SOD activity also in ethanol-containing medium, whereas we achieved 125 U/mg protein SOD activity with glycerol-containing medium. Th ese comparative results seem to be striking, since they were obtained without additional oxidative stress.…”
Section: Discussionmentioning
confidence: 66%
“…In terms of CAT activities, 66.9 U/mg was obtained with Escherichia coli B (Misra and H ö fer 1975), while 93.7 NU/mg with Cordyceps militaris (Wang et al 2005); additionally, 90 NU/mg protein was obtained with Stenotrophomonas maltophilia (L ü et al 2008). Using R. glutinis, Koleva et al (2008) reached 22 U/mg protein of CAT activity in ethanol-containing medium while we obtained 113 U/mg protein CAT activity in glycerol-containing medium. In terms of SOD activities, 90 U/mg protein was reported with Aspergillus niger (Tsekova and Todorova 2002), while 44.3 U/mg with Cordyceps militaris (Wang et al 2005) and 150 U/mg with Stenotrophomonas maltophilia (Tsekova and Todorova 2002), most of which were exposed to an oxidative stress inducer.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recent genetic and biochemical experiments revealed that in Rhodotorula mucilaginosa and Rhodotorula graminis changes in the structure of the SOD1 gene generate stop codons at different positions, which correlates with the absence of peptides or active proteins in the cells. however, for other basidiomycetous yeasts, such as R. glutinis and U. puniceus, the cloned nucleotide sequence contains all necessary information to produce a functional protein (16,20). Moreover, studies with S. cerevisiae cells lacking the cytosolic Sod1, showed that cadmium was removed twice as effectively as in the control strain, while those deficient in the mitochondrial Sod2 exhibited poor metal absorption (1).…”
Section: Oxygen Metabolism Affects Growth On CDmentioning
confidence: 99%
“…(16) The thermostability of SOD enzymes was analyzed in the range of 30°C, 50°C and 75°C. A spectrophotometrical analysis showed that average 21.55% of the total enzyme activity remains after treatment with 75C for 10 minutes when cells were cultivated on methanol, glucose and glycerol.…”
Section: Influence Of Carbon Source On Growth Of H Polymorpha and Somentioning
confidence: 99%